LEGAL DYNAMICS RELATED TO HOTEL BUSINESS STANDARDIZATION IN THE HALAL TOURISM INDUSTRY IN INDONESIA - Mohammad Fateh; Heris Suhendar; Rifdah Nabilatuzain (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
This study aims to analyze the dynamics of hotel business standardization regulations in the halal tourism industry in Indonesia, examine their legal implications, and formulate a more adaptive and sustainable regulatory model. This study uses a normative juridical method with a statutory regulatory approach and a conceptual approach analyzed qualitatively through descriptive-analytical and prescriptive methods. The results indicate a transformation in the regulatory paradigm from a Sharia-compliant regulatory model to a market-oriented service-based model, characterized by a shift in terminology from Sharia tourism, halal tourism, to Muslim-friendly tourism. This transformation has resulted in a weakening of the binding power of norms (regulatory dilution) and the emergence of an imbalance between economic interests, religious values, and legal certainty (regulatory imbalance). In this context, this study proposes a hybrid regulatory model as a new formulation that integrates compliance-based and service-based approaches. This model places Sharia principles as the normative foundation while providing flexibility for business actors in responding to the dynamics of the halal tourism industry. Thus, this research provides a conceptual contribution to the development of halal tourism law, particularly in formulating a hotel business standardization model that is able to maintain a balance between industrial competitiveness and the integrity of sharia values.